Psychosocial Factors That Influence Health Care Use and Self-Management for African American and Latino Men With Type 2 Diabetes: An Exploratory Study. Issue 2 (June 2015) - Hawkins, Jaclynn; Watkins, Daphne C.; Kieffer, Edith; Spencer, Michael; Espitia, Nicolous; Anderson, Michael
The purpose of this study was to explore the psychosocial factors that influence diabetes self-management and health care utilization among men of color with type 2 diabetes. Data were collected from focus groups with African American men ( n = 9) and Latino men ( n = 13) who were part of a diabetes intervention. Sessions were analyzed using thematic content analysis techniques. Five themes were discussed in focus groups, including (a) social support as a motivator, (b) patient–provider relationships as facilitators of healthy behaviors, (c) immigration status and access to resources, (d) waiting until symptoms became severe before seeking medical attention, and (e) structural barriers. Public health interventions may need to tailor interventions to address the specific needs of men of color.